Variations in OsSPL10 confer drought tolerance by directly regulating OsNAC2 expression and ROS production in rice. Issue 4 (17th January 2023) - Li, Yingxiu; Han, Shichen; Sun, Xingming; Khan, Najeeb Ullah; Zhong, Qun; Zhang, Zhanying; Zhang, Hongliang; Ming, Feng; Li, Zichao; Li, Jinjie
ABSTRACT: Drought is a major factor restricting the production of rice ( Oryza sativa L.). The identification of natural variants for drought stress‐related genes is an important step toward developing genetically improved rice varieties. Here, we characterized a member of the SQUAMOSA PROMOTER BINDING PROTEIN‐LIKE (SPL) family, OsSPL10, as a transcription factor involved in the regulation of drought tolerance in rice. OsSPL10 appears to play a vital role in drought tolerance by controlling reactive oxygen species (ROS) production and stomatal movements. Haplotype and allele frequency analyses of OsSPL10 indicated that most upland rice and improved lowland rice varieties harbor the OsSPL10 Hap1 allele, whereas the OsSPL10 Hap2 allele was mainly present in lowland and landrace rice varieties. Importantly, we demonstrated that the varieties with the OsSPL10 Hap1 allele showed low expression levels of OsSPL10 and its downstream gene, OsNAC2, which decreases the expression of OsAP37 and increases the expression of OsCOX11, thus preventing ROS accumulation and programmed cell death (PCD). Furthermore, the knockdown or knockout of OsSPL10 induced fast stomatal closure and prevented water loss, thereby improving drought tolerance in rice. Based on these observations, we propose that OsSPL10 confers drought tolerance by regulating OsNAC2 expression and that OsSPL10 Hap1 could be a valuable haplotype for the genetic improvement of drought tolerance in rice. Abstract : The rice transcription factor SQUAMOSA PROMOTER BINDING PROTEIN‐LIKE 10 (OsSPL10) confers drought tolerance by regulating OsNAC2 expression and reactive oxygen species accumulation. Haplotype and allele frequency analyses of OsSPL10 indicate that OsSPL10 Hap1 could be a valuable haplotype for genetic improvement of drought tolerance in rice.